Exogenous Carbon Monoxide Produces Rapid Antidepressant- and Anxiolytic-Like Effects - Luo, Yixiao; Ullah, Rafi; Wang, Jinfeng; Du, Yuru; Huang, Shihao; Meng, Li; Gao, Yuan; Gong, Miao; Galaj, Ewa; Yin, Xi; Shi, Haishui (Frontiers in Pharmacology, 2021)
Carbon monoxide, a byproduct of heme catalyzed by heme oxygenase (HO), has been reported to exert antioxidant and anti-inflammatory actions and to produce significant neuroprotective effects. The potential effects of CO and even HO on depressive-like behaviors are still poorly understood. Using adeno-associated virus (AAV)-mediated overexpression of HO-1, systemic CO-releasing molecules CO-RM, CO-rich saline or CO gas treatment procedures in combination with hydrogen peroxide (H2O2)-induced PC12 cell injury model and lipopolysaccharide (LPS)-induced depression mice model, the present study aimed to investigate the potential antidepressant- and anxiolytic-like effects of endogenous and exogenous CO administration in vivo and in vitro. The results of in vitro experiments showed that both CO-RM-3 and CO-RM-A1 pretreatment could block H2O2-induced cellular injuries by increasing cell survival and decreasing cell apoptosis and necrosis. Likely to the effects of CO-RM-3 and CO-RM-A1 pretreatment, AAV-mediated HO-1 overexpression in dorsal hippocampus produced significant antidepressant-like activities in mice under normal condition. Further investigation also showed that CO-gas treatment could significantly block LPS-induced depressive- and anxiety-like behaviors in mice. Taken together, our results suggest that activation of HO-1 and/or exogenous CO administration produce protective effects and exerts antidepressant- and anxiolytic-like effects. These data provide a novel mechanism that HO-1/CO system, could be a promising therapeutic target for treatment of depression and anxiety.